Patterns of Antemortem Tooth Loss in Late Prehistoric West-central Tennessee - Maria Ostendorf Smith; Tracy K. Betsinger (Dental Anthropology Association, 2021)
The later prehistoric subsistence-settlement pattern in the Kentucky Lake Reservoir (KLR) of northern west-central Tennessee is of interest as human occupation inexplicably terminates by AD 1450 as part of a larger regional depopulation. Antemortem tooth loss (ATL) collectively and by tooth type was identified in four site samples from the KLR. These are a Late Woodland (AD 600-900) sample (Hobbs) and three Middle Mississippian period (AD 1100- 1400) hierarchically organized and presumptively maize agriculturalist samples (Link/Slayden, Gray Farm , Thompson Village). ATL prevalence in the Hobbs sample is consistent with a native crop and seasonal foraging economy. The ATL in the Link sample is more congruent with the pre-maize Late Woodland sample than the essentially contemporaneous Gray Farm site sample. Thompson Village, a later-dated satellite community of the Gray Farm polity, exhibits significantly fewer ATL than the Gray Farm sample. This may flag climate-influenced agricultural shortfall of dietary carbohydrates later in the occupation sequence. Additionally, males in the Gray Farm site sample have significantly more ATL than males in the other two Mississippian samples. The patterns suggest regional, possibly shortfall mitigated, differences in maize intensification with a polity-specific male-focused maize consumption in the Gray Site.